DESAIN JARINGAN INTERNET INDIHOME DI PERUMAHAN MANGGAR PERMAI AMBULU MENGGUNAKAN ALGORITMA K-MEANS DAN KRUSKAL - Reggy Valentinnes Septa Jeniusa; Kiswara Agung Santoso; Kusbudiono Kusbudiono (UPT Penerbitan Universitas Jember, 2022)
Based on the survey results of the Association of Indonesian Internet Service Providers, internet users are increasing reaching 196.7 million people. This community need is the driving force for PT. Telkom to overcome the need for internet access, namely the presence of Indihome. The Indihome internet network is distributed to several houses through ODP. The grouping of houses on ODP is based on the closest distance using the k-means algorithm. Meanwhile, minimizing the use of Indihome internet cables using the Kruskal algorithm. The data used in this study are house coordinates data obtained from the Google Earth application. The data is processed using the k-means algorithm, then continued using the Kruskal algorithm. The results of the research are clustering in houses with ODP formed 16 clusters which are processed using the k-means algorithm and stop at the 5th iteration. The ODP used has capacities of 8 and 12. ODP 1, 2, 4, 5, 8, 9, 11, 12, 13, 14, 15, 16 have capacities of 8. While ODP 3, 6, 7, 10 has a capacity of 12. Fiber optic cable between ODP is processed using the Kruskal algorithm and produces a minimum weight of 0.006601782 or ± 735 meters. Keywords: Indihome, K-Means Algorithm, Kruskal Algorithm